Building cultural nationalism in Malaysia : identity, representation, and citizenship - Daniels, Timothy P., 1960- (East Asia (New York, N.Y.), 2005)
This text contains an examination of processes of cultural citizenship in peninsular Malaysia. In particular, it focuses upon the diverse residents of the southwestern state of Melaka and their negotiations of belonging in Malaysian society.